The Analysis of Fillers on Live Youtube Video Grammar Lesson - Aliyah, Sekar Lathifatul; Farikah, Farikah; Yosintha, Rolisda (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Fillers are words, phrases, or even sounds which are utilized to fill the silence phase of the speaking process that always be viewed as a lack of speaking skills or disfluency. There are two types of fillers based on Rose (1998) which are unlexicalized fillers and lexicalized fillers. However, there are 5 functions of fillers based on Stenstrom (1994) namely, hesitating, empathizing, mitigating, editing terms, and time-creating devices. Furthermore, this study intends to uncover the types of fillers and the functions of fillers utilized by Aga Murdoch as an English native speaker in her live YouTube video. In this live YouTube video, she teaches about English grammar especially tenses. Therefore, the utterances that utilized in this teaching is a source of data that will be studied. Content analysis and qualitative approach are used as the methodology of this study. However, this study also uses data reduction, data presentation and drawing conclusion to manage the data. In order to ensure the validity and trustworthiness of the results, this study will also utilize investigator triangulation. On the other hand, the outcome of this study showed that Aga Murdoch used 147 fillers. In this study, there were 67 unlexicalized fillers dan 80 lexicalized fillers. As a conclusion, fillers have a prominent role to maintain a good speaking process. Besides, several aspects should be fulfilled when using fillers in daily interactions. Moreover, this study is expected to enhance speaking skill awareness and provide more comprehension regarding filler